Visual rotation axis and body position relative to the gravitational direction: Effects on circular vection - Tanahashi, Shigehito (Pion, 2012)
The visual–vestibular conflict theory asserts that visual–vestibular conflicts reduce vection and that vection strength is reduced with an increasing discrepancy between actual and expected vestibular activity. Most studies support this theory, although researchers have not always accepted them. To ascertain the conditions under which the theory of the visual–vestibular conflict can be applied, we measured circular vection strength accompanied by manipulation of the visual–otolith conflict by setting the axes of visual global motion (pitch, roll, and yaw) as either earth-horizontal or earth-vertical, using three different body positions (supine, left-lateral recumbent, and sitting upright). When the smaller stimulus was used, roll vection strength was greater with the visual–otolith conflict than without it, which contradicts the visual–vestibular conflict theory. We confirmed this result, as observers were able to distinguish circular vection from an illusory body tilt. Moreover, with observers in an upright position, the strength of yaw vection, which does not involve the visual–otolith conflict, increased and was almost equal to that of roll vection, which involves the visual–otolith conflict. This suggests that if the visual stimulus covers the entire visual field, the strength of circular vection around the earth-vertical axis exceeds that around the earth-horizontal axis, which is a finding consistent with the visual–vestibular conflict theory.